Innovation Networks: the Contribution of Partnerships to Innovative Performance of Firms in the Brazilian Electrical-Electronics Industry - Silvye Ane Massaini; Fábio Lotti Oliva (BBR: Brazilian Business Review)
Innovation networks have been identified in the literature as a way to complement firms’ innovative capabilities through collaboration with other partners. To provide empirical evidence for this assertion, this paper investigates the contribution of partners established in innovation networks for innovative performance of firms in the Brazilian electricalelectronics industry. For this purpose, we carried out an exploratory and descriptive survey among 185 companies. The data were analyzed using structural equation modeling (SEM). As the main findings, we observed that the establishment of collaborative relationships with customers, competitors and universities/research institutions can contribute to organizational and process innovation. However, despite obtaining some significant results concerning the contribution of different partners in the network, electrical-electronics industry companies also attach great importance to internal activities to develop their innovations.